A survey on the relationship between attitude and motivation to the achievement of english among UPSR students in Felda Tenggaroh Mersing, Johore - 231709 Nur Ahlina Ng Abdullah (Skudai : UTM, 1999)
Project Paper (Bachelor of Science with Education (TESL)) - Universiti Teknologi Malaysia, 1999